2018
DOI: 10.11648/j.ajam.20180603.13
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Susceptible Human Immigrants on the Spread and Dynamics of Malaria Transmission

Abstract: Malaria is one of infectious diseases and has become the most public health issue especially in developing countries. Mathematically, the spread of malaria can be modeled to predict the dynamics of the outbreak of the disease. The present research studies the impact of migration of susceptible population on the dynamics of malaria transmission. In this paper an improved mathematical model is constructed based on a set of reasonable assumptions. Validity of the model is proved by verifying positivity of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…the parameters d = P K usually called the carrying capacity [31]. Hence all feasible solutions set of the human population of the model (1) enters the region.…”
Section: Invariant Regionmentioning
confidence: 99%
“…the parameters d = P K usually called the carrying capacity [31]. Hence all feasible solutions set of the human population of the model (1) enters the region.…”
Section: Invariant Regionmentioning
confidence: 99%
“…Using the interactions illustrated by Figure 1, the dynamics of the transmission given by the system of non linear differential equations (1).…”
Section: The Mathematical Modelmentioning
confidence: 99%
“…In this subsection we provide further simulations showing the varying effects of the immunity parameters (µ, λ, σ and θ) on the behaviour of the system (1). We analyze these effects for R 0 > 1.…”
Section: The Varying Effects Of the Immunity Parameters On The Behavimentioning
confidence: 99%
“…It is already shown that the DFE of model ( 1) -( 4) is given bf e = 9 ⁄ , 0, 0, 0A. Now, following [5][6][7][8] the stability analysis of DFE is conducted and the results are presented in the form of theorems and proofs in the following.…”
Section: Stability Analysis Of the Disease Free Equilibriummentioning
confidence: 99%